2020
DOI: 10.2147/pgpm.s234910
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>CYP2C19*17</em> May Increase the Risk of Death Among Patients with an Acute Coronary Syndrome and Non-Valvular Atrial Fibrillation Who Receive Clopidogrel and Rivaroxaban</p>

Abstract: The aim of this study is to assess the influence of gene CYP2C19, CYP3A4, CYP3A5 and ABCB1 polymorphisms on clopidogrel antiplatelet activity, rivaroxaban concentration equilibrium, and clinical outcomes among patients with acute coronary syndrome and non-valvular atrial fibrillation. Methods: In the multicenter prospective registry study of the efficacy and safety of a combined antithrombotic therapy 103 patients with non-valvular atrial fibrillation both undergoing or not a percutaneous coronary intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
9
0
2
Order By: Relevance
“…The gene polymorphism of ABCB1 may cause P-gp expression to (Sychev et al, 2020;Wang et al, 2021). The genetic factor CYP2C19 was proved to be associated with the risk of bleeding complications in situations of rivaroxaban antithrombotic therapy (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The gene polymorphism of ABCB1 may cause P-gp expression to (Sychev et al, 2020;Wang et al, 2021). The genetic factor CYP2C19 was proved to be associated with the risk of bleeding complications in situations of rivaroxaban antithrombotic therapy (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent trial found that a clopidogrel prescription after STEMI, using genotype-guided point of care, produced less bleeding and equal ischaemic events when compared with ticagrelor or prasugrel [99]. Moreover, similar results were documented in AF patients with interventional treatment [100,101]. Thus, genetic testing could be the answer when the thrombotic risk is not high and using clopidogrel in a DAT regimen represents the best option to reduce bleeding complications.…”
Section: Potent P2y12 Inhibitors Versus Clopidogrelmentioning
confidence: 93%
“…The POPular Genetics trial found that genotype-guided clopidogrel prescription after ST-elevation myocardial infarction (STEMI) without an indication for OAC showed equal MACE, but less bleeding, compared to standard treatment with ticagrelor or prasugrel [ 38 ]. A suggestion of benefit has also been described in patients with AF undergoing PCI [ 39 , 40 ]. Therefore, if available, before prescribing more potent P2Y 12 inhibition, genetic testing might be reasonable to consider if equal antithrombotic efficacy can be expected with clopidogrel to reduce bleeding complications and in the absence of high ischaemic risk.…”
Section: Choice Of Antiplatelet Agentmentioning
confidence: 99%